Synthetic Biology and Ethics: Past, Present, and Future - Häyry, Matti (Cambridge quarterly of healthcare ethics, 2017)
This article explores the ethical issues that have been identified in emerging technologies, from early genetic engineering to synthetic biology. The scientific advances in the field form a continuum, and some ethical considerations can be raised time and again when new developments occur. An underlying concern is the cumulative effect of scientific advances and ensuing technological innovation that can change our understanding of life and humanity.